2012
DOI: 10.1063/1.4756800
|View full text |Cite
|
Sign up to set email alerts
|

Condensation heat transfer on two-tier superhydrophobic surfaces

Abstract: We investigated water vapor condensation on a two-tier superhydrophobic surface in an environmental scanning electron microscope (ESEM) and in a customer-designed vapor chamber. We have observed continuous dropwise condensation (DWC) on the textured surface in ESEM. However, a film layer of condensate was formed on the multiscale texture in the vapor chamber. Due to the filmwise condensation, the condensation heat transfer coefficient of the superhydrophobic surface is lower than that of a flat hydrophobic sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
82
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(88 citation statements)
references
References 17 publications
5
82
0
1
Order By: Relevance
“…36,56 How to avoid the ooding of nano-textures is one of the key issues to consider in the design and preparation of novel super-hydrophobic textured surfaces. 1-3 And such drops aer coalescence could jump and shi away from the surfaces 1-3,20,21,27,54,55 so that efficient dropwise condensation may be realized.…”
Section: Wetted States Of Condensed Droplets On Rough Surfaces and Thmentioning
confidence: 99%
“…36,56 How to avoid the ooding of nano-textures is one of the key issues to consider in the design and preparation of novel super-hydrophobic textured surfaces. 1-3 And such drops aer coalescence could jump and shi away from the surfaces 1-3,20,21,27,54,55 so that efficient dropwise condensation may be realized.…”
Section: Wetted States Of Condensed Droplets On Rough Surfaces and Thmentioning
confidence: 99%
“…Different from traditional superhydrophobic surfaces, which are characterized by the bouncing or rolling off of deposited millimeter-size large drops, [32,33] CMDSP surfaces support the self-removal capability of smallscale condensate microdrops. It has been reported that classical superhydrophobic lotus leaves (Figure 1a), [34][35][36][37] as well as artificial surfaces consisting of hierarchical micro-and nanostructures, [38] one-tier microstructures, [39][40][41][42][43] or nanostructures [44,45] with larger characteristic interspaces, present a low-adhesivity property to the deposited water macrodrops, but become highly adhesive to condensed microdrops (Figure 1b). This is because moisture easily penetrates the microscale valleys or cavities.…”
mentioning
confidence: 99%
“…Most of researchers have focused on fabrication of a non-wetting surface with high water contact angle (WCA), which is measured by a sessile drop. For a couple of decades, there are various well-known methods such as organic promoters [2][3][4][5], fatty acids [6], noble-metal electroplating (gold, silver, and platinum) [7][8][9][10][11][12], hydrophobic polymer coating (polytetrafluoroethylene (PTFE) [13][14][15]), and micro/nano composite-structured surfaces (cuprous oxide [16][17][18][19][20][21], carbon nanotube (CNT) [22]). …”
Section: Introductionmentioning
confidence: 99%